Synthesis, characterization and catalytic application of Ru-II-ethylenediamine complex - mesoporous silica as heterogeneous catalyst system in chemo-selective hydrogenation of alpha,beta-unsaturated carbonyl compounds - Ghosh, Anirban; Kumar, R (Microporous and Mesoporous Materials, 2005)
An efficient heterogeneous catalyst system for chemo-selective hydrogenation of alpha,beta-unsaturated aldehydes was synthesized, involving anchoring of a Ru-II-phosphine complex on the inner surfaces of organo-functionalized (propylamine and propylethylenediamine) mesoporous MCM-41 and MCM-48 materials. Powder XRD, SEM and TEM experiments reveal highly ordered hexagonal and cubic patterns of the organically modified MCM-41 and MCM-48 materials, respectively, even after incorporation of Ru complexes. Moreover, the integrity of the Ru complex was retained after anchoring into the mesoporous hosts, which was supported by FTIR, P-31 CP MAS NMR and XPS analyses. This heterogeneous catalyst shows promising activity and chemo-selectivity towards hydrogenation of carbonyl groups in alpha,beta-unsaturated aldehydes. The effects of reaction temperature, reaction time and hydrogen pressure on the activity and selectivity were studied in detail. The anchored solid catalysts can be recycled effectively and reused several times without any loss in activity and selectivity. Although, the initial activity of the same Ru complex when grafted onto the organically modified surfaces of fumed silica is comparable to corresponding MCM41/MCM-48 catalysts, the activity and chemo-selectivity significantly decrease during recycle of the catalyst due to leaching. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: chemo-selective; heterogeneous catalysis; Heterogenization; Hydrogenation; mesoporous materials; organo-functionalization; Ru-II-ethylenediamine complex; unsaturated aldehyde

Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor